2021
DOI: 10.3390/molecules26040888
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Apoptotic Activity, and Antiparasitic Effects of Ferula macrecolea Essential Oil against Echinococcus granulosus Protoscoleces

Abstract: Background: Today, the present protoscolicidals used to minimize the serious risks during hydatid cyst surgery are not completely safe and have various adverse side effects. The present study aimed to evaluate the chemical composition and apoptotic activity of Ferula macrecolea essential oil (FMEO) as well as its in vitro and ex vivo protoscolicidal effects against hydatid cyst protoscoleces. Methods: Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine the chemical composition of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Moreover, in a study carried out by Khanmohammadi et al (2014), the methanol extract of F. szowitsiana displayed potent antiparasitic effects against trophozoites of Trichomonas vaginalis with an IC 50 value of 0.360 mg/mL ( Khanmohammadi et al, 2014 ). Recently, Alyousif et al (2021) reported that F. macrecolea essential oil displayed effective in vitro and ex vivo protoscolicidal activity against Echinococcus granulosus protoscoleces and completely eliminated the protoscoleces at the concentrations of 150 and 300 μL/mL ( Alyousif et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a study carried out by Khanmohammadi et al (2014), the methanol extract of F. szowitsiana displayed potent antiparasitic effects against trophozoites of Trichomonas vaginalis with an IC 50 value of 0.360 mg/mL ( Khanmohammadi et al, 2014 ). Recently, Alyousif et al (2021) reported that F. macrecolea essential oil displayed effective in vitro and ex vivo protoscolicidal activity against Echinococcus granulosus protoscoleces and completely eliminated the protoscoleces at the concentrations of 150 and 300 μL/mL ( Alyousif et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results could be noticed with these classes in many Ferula species. For instance, terpinolene (77.62%) was the major component in F. macrecolea [ 15 ], while β-pinene (60.84%) was the predominant metabolite in F. gummosa [ 16 ]. In F. tunetana , α-pinene (39.8%) was the main component [ 17 ] and α-thujene (13.5%) is present in the highest concentration in F. tingitana [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The helium flow rate was 1 ml/min with a 70 eV ionization voltage. The compositions were identified through the evaluation of the retention times and mass spectra with those of the WILEY 09 and NIST 11 mass spectral databases ( Adams, 2004 ; NIST, N., 2014 ; Alyousif et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%